Judicial Challenges in Determining Marriage Dispensation under PERMA Number 5 of 2019: The Conflict Between Legal Certainty and Child Protection Principles in Indonesia - Fatmawati; Iin Ratna Sumirat; Sayehu; Rohmani (UIN Jurai Siwo Lampung, 2026)
Judges in Indonesia are frequently confronted with a dilemma between legal certainty and child rights protection. Law No. 16 of 2019 establishes the minimum age for marriage as a form of protection, yet it remains open to dispensation under specific circumstances. This study analyzes the challenges faced by judges in handling marriage dispensation cases and evaluates whether court rulings align with the principle of the best interests of the child. Employing a normative juridical research method with conceptual and statutory approaches, this study is supported by an analysis of court rulings, including Decision No. 85/Pdt.P/2025/PA.Srg as a case study. The findings reveal that in practice, positive law is not the sole factor influencing judicial decisions; social, cultural, moral, and Islamic values also play a significant role. Extensive judicial discretion has the potential to shift the orientation of child protection toward the legitimization of child marriage if it is not restricted by measurable indicators regarding the best interests of the child. Therefore, harmonization between legal certainty and child protection principles is required through the reinforcement of judicial guidelines to ensure that marriage dispensation rulings do not adversely affect children's futures.